Latex composition, foam rubber, and puff, and method for producing latex composition

A latex composition with a polymer latex and alkali metal salt of a polybasic acid addresses storage stability and molding issues, ensuring excellent gelling and shrinkage suppression for high-quality foam rubber production.

JP7604995B2Active Publication Date: 2024-12-24ZEON CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021056239
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2024-12-24
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

Existing latex compositions used for foam rubber manufacturing lack sufficient storage stability and exhibit poor gelling and shrinkage suppressing properties during foam rubber molding.

Method used

A latex composition containing a polymer latex and a specific amount of an alkali metal salt of a divalent or higher polybasic acid, with a solid content concentration of 60% or more and viscosity of 1500 cps or less, is developed, using components like nitrile group-containing conjugated diene copolymers and surfactants with a sulfonate structure.

Benefits of technology

The composition achieves excellent storage stability, gelling properties, and shrinkage suppression during foam rubber molding, enabling high-quality foam rubber production with improved texture and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604995000001
    Figure 0007604995000001
Patent Text Reader

Abstract

To provide a latex composition excellent in storage stability, gelation properties, and shrinkage suppressing property during foam rubber molding.SOLUTION: There is provided a latex composition which contains a polymer latex and 0.5-20 pts.wt. of an alkali metal salt of a divalent or higher polybasic acid based on 100 pts.wt. of a polymer component in the polymer latex and has a solid content concentration of 60 wt.% or more and a viscosity at a temperature of 25°C of 1,500 cps or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a latex composition, a foam rubber, and a puff, and a method for making the latex composition. [Background technology]

[0002] Foam rubber (rubber foam) produced from polymer latex is used in a variety of applications, including mattresses, cosmetic sponges (puffs), rolls, and shock absorbers.

[0003] As a polymer latex for obtaining such a rubber foam, from the viewpoint of good oil resistance, acrylonitrile-butadiene copolymer rubber (NBR) latex and a latex composition containing the same have been used conventionally (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5859693 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the latex composition disclosed in the above Patent Document 1 does not have sufficient storage stability, and therefore, there is a need to improve the storage stability. In addition, when the latex composition is used for foam rubber, it is required to have excellent gelling properties and excellent shrinkage suppression properties during foam rubber molding.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a latex composition which is excellent in storage stability, gelling property and shrinkage suppression property during foam rubber molding. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the present inventors have found that the above-mentioned object can be achieved by a latex composition which contains a polymer latex and a specific amount of an alkali metal salt of a divalent or higher polybasic acid, and has a solid content concentration and a viscosity within specific ranges, and have thus completed the present invention.

[0008] That is, according to the present invention, there is provided a latex composition comprising a polymer latex and 0.5 to 20 parts by weight of an alkali metal salt of a divalent or higher polybasic acid relative to 100 parts by weight of a polymer component in the polymer latex, the latex composition having a solid content concentration of 60% by weight or more and a viscosity at 25°C of 1500 cps or less.

[0009] The latex composition of the present invention is preferably a latex of a nitrile group-containing conjugated diene copolymer. The latex composition of the present invention preferably has a viscosity at 25° C. of 1000 cps or less. In the latex composition of the present invention, the divalent or higher polybasic acid is preferably at least one selected from the group consisting of phosphoric acid and sulfuric acid. In the latex composition of the present invention, the alkali metal is preferably potassium.

[0010] According to the present invention, there is also provided a foam rubber obtained by foam molding the above latex composition. Furthermore, according to the present invention, there is provided a puff obtained by foam molding the above-mentioned latex composition. Further, according to the present invention, there is provided a method for producing a latex composition, comprising: a preparation step of preparing a polymer latex; and a particle size enlargement / concentration step of adding a salt of a divalent or higher polybasic acid and an alkali metal to the polymer latex, and concentrating the resulting mixture to obtain a latex composition containing an enlarged polymer latex, having a solid content of 60% by weight or more and a viscosity of 1500 cps or less at 25°C, wherein in the particle size enlargement / concentration step, 0.5 to 20 parts by weight of the salt of a divalent or higher polybasic acid and an alkali metal is added relative to 100 parts by weight of the polymer component in the polymer latex. Effect of the Invention

[0011] According to the present invention, it is possible to provide a latex composition which is excellent in storage stability, gelling property, and shrinkage suppression property during molding of foam rubber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The latex composition of the present invention contains a polymer latex and 0.5 to 20 parts by weight of an alkali metal salt of a divalent or higher polybasic acid relative to 100 parts by weight of a polymer component in the polymer latex, has a solid content concentration of 60% by weight or more, and has a viscosity at 25°C of 1500 cps or less.

[0013] <Polymer latex> The polymer latex contained in the latex composition of the present invention is a dispersion in which polymer particles are dispersed in water.

[0014] The polymer constituting the polymer particles is not particularly limited, but examples thereof include nitrile group-containing conjugated diene copolymers; styrene-butadiene copolymers; synthetic polyisoprene; styrene-isoprene-styrene block copolymers (SIS); polybutadiene; natural rubber; deproteinized natural rubber, etc. Among these, nitrile group-containing conjugated diene copolymers or styrene-butadiene copolymers are preferred. The obtained foam rubber can be excellent in texture and durability such as oil resistance and abrasion resistance, so nitrile group-containing conjugated diene copolymers are more preferred. The polymer constituting the polymer particles may be one type alone or two or more types.

[0015] The polymer constituting the polymer particles may have a modified group such as a carboxyl group, but from the viewpoint of gelation, a polymer without a carboxyl group is preferable. The polymer without a carboxyl group may be any polymer that does not substantially have a carboxyl group, and may contain a carboxyl group in an amount that is attributable to impurities, etc. (for example, less than 0.05% by weight in terms of monomer units).

[0016] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer and an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0017] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably 20 to 95% by weight, more preferably 30 to 85% by weight, and even more preferably 40 to 80% by weight. By setting the content of the conjugated diene monomer unit within the above range, the obtained foam rubber can be excellent in texture and durability.

[0018] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer unit formed by the ethylenically unsaturated nitrile monomer in the nitrile group-containing conjugated diene copolymer is preferably 5 to 80% by weight, more preferably 15 to 70% by weight, and even more preferably 20 to 60% by weight. By setting the content ratio of the ethylenically unsaturated nitrile monomer unit in the above range, the obtained foam rubber can be excellent in texture and durability.

[0019] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include ethylenically unsaturated carboxylic acids such as (meth)acrylic acid, (anhydride) maleic acid, fumaric acid, and itaconic acid; mono- or di-alkyl esters of ethylenically unsaturated carboxylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, mono- or dimethyl maleate, mono- or di-n-butyl maleate, mono- or diethyl fumarate, mono- or di-n-butyl fumarate, and mono- or di-n-butyl itaconate; and ethylenically unsaturated carboxylic acids such as methoxyacrylate, ethoxyacrylate, and methoxyethoxyethyl acrylate. Examples of the monomers include alkoxyalkyl esters of acids; (meth)acrylates having a hydroxyalkyl group such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; glycidyl (meth)acrylate; (meth)acrylamide, N-methylol (meth)acrylamide, and N-butoxymethyl (meth)acrylamide (meth)acrylamide and its derivatives; acrylates having an amino group such as dimethylaminomethyl acrylate and diethylaminomethyl acrylate; aromatic vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, and chlorostyrene; α-olefins such as ethylene and propylene; and non-conjugated diene monomers such as dicyclopentadiene and vinylnorbornene. These monomers can be used alone or in combination of two or more. The content of other monomer units formed by other ethylenically unsaturated monomers in the nitrile group-containing conjugated diene copolymer is preferably 40% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less. By setting the content ratio of the other monomer units within the above range, the obtained foam rubber can be made excellent in feel and durability.

[0020] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing styrene with 1,3-butadiene as a conjugated diene monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0021] The polymer latex contained in the latex composition of the present invention may further contain a surfactant having a sulfonate structure.

[0022] Surfactants with a sulfonate structure contain a sulfonate anion group (-SO3 - ) and a counter cation. Examples of surfactants having a sulfonate structure include naphthalenesulfonic acid formalin condensate salts such as β-naphthalenesulfonic acid formalin condensate sodium salt (NASF); linear or branched alkylbenzenesulfonate salts such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinate salts such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctyl sulfosuccinate; alkylnaphthalenesulfonate salts such as sodium alkylnaphthalenesulfonate; alkylsulfuric acid ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; and polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate. The surfactant having a sulfonate structure can be used alone or in combination of two or more kinds.

[0023] As the surfactant having a sulfonate structure, a naphthalenesulfonic acid formalin condensate salt, an alkylnaphthalenesulfonate, or a linear alkylbenzenesulfonate can be used since it is possible to obtain a latex composition having excellent storage stability, gelling properties, and shrinkage suppression properties during foam rubber molding. Naphthalenesulfonic acid formalin condensate sodium salt or alkylnaphthalenesulfonic acid sodium salt is more preferable, β-naphthalenesulfonic acid formalin condensate sodium salt (NASF) or alkylnaphthalenesulfonic acid sodium salt is further preferable, and β-naphthalenesulfonic acid formalin condensate sodium salt (NASF) is particularly preferable.

[0024] In the case where the polymer latex contains a surfactant having a sulfonate structure, the content ratio of the surfactant having the sulfonate structure is preferably 0.15 parts by weight or more and less than 5.0 parts by weight based on 100 parts by weight of the polymer component contained in the polymer latex. By setting the content ratio of the surfactant having a sulfonate structure within the above range, a latex composition having excellent storage stability, gelling properties, and shrinkage suppression properties during foam rubber molding can be obtained. The content ratio of the surfactant having a sulfonate structure is more preferably 0.1 to 4.0 parts by weight, and even more preferably 1.0 to 3.0 parts by weight based on 100 parts by weight of the polymer component in the polymer latex.

[0025] <Alkali metal salts of divalent or higher polybasic acids> The latex composition of the present invention contains the above-mentioned polymer latex and an alkali metal salt of a divalent or higher polybasic acid, and contains 0.5 to 20 parts by weight of the alkali metal salt of a divalent or higher polybasic acid per 100 parts by weight of the polymer latex. In the present invention, by containing the alkali metal salt of a divalent or higher polybasic acid together with the polymer latex, the latex composition can have excellent storage stability, excellent gelling properties, and shrinkage suppression properties during foam rubber molding.

[0026] If the amount of the alkali metal salt of the divalent or higher polybasic acid is less than 0.5 parts by weight, the viscosity becomes too high when the solid content is 60% by weight or more, making it difficult to use it for foam rubber applications. If the amount of the alkali metal salt of the divalent or higher polybasic acid is more than 20 parts by weight, coagulation of the latex may occur, which is not preferable.

[0027] In addition, the alkali metal salt of a divalent or higher polybasic acid has the effect of unifying polymer particles constituting the polymer latex, thereby enlarging the particle size. Therefore, the polymer latex constituting the latex composition of the present invention may be an enlarged polymer latex in which polymer particles constituting the polymer latex obtained by emulsion polymerization are unified and the particle size is enlarged.

[0028] As the divalent or higher polybasic acid, at least one selected from the group consisting of carbonic acid, sulfuric acid, phosphoric acid, sulfurous acid, thiosulfuric acid, and chromic acid can be used, and sulfuric acid or phosphoric acid is preferable, and phosphoric acid is particularly preferable. By using the above-mentioned as the divalent or higher polybasic acid, it is possible to further improve storage stability, gelling property, and shrinkage suppression during foam rubber molding. As the alkali metal, lithium, sodium, or potassium is preferable, and potassium is particularly preferable.

[0029] The latex composition of the present invention preferably contains, as the alkali metal salt of a divalent or higher polybasic acid, at least one selected from the group consisting of trisodium phosphate, tripotassium phosphate, sodium sulfate, and potassium sulfate, and more preferably contains at least one selected from the group consisting of tripotassium phosphate and potassium sulfate.

[0030] The latex composition of the present invention contains preferably 0.5 parts by weight or more and less than 10 parts by weight, more preferably 0.5 to 5 parts by weight, of an alkali metal salt of a divalent or higher polybasic acid based on 100 parts by weight of the polymer latex.

[0031] Moreover, the latex composition of the present invention has a solid content concentration of 60% by weight or more and a viscosity of 1500 cps or less at 25° C. By having the solid content concentration and the viscosity at 25° C. within this range, when the latex composition of the present invention is used for foam rubber applications, a foam rubber having sufficient strength can be appropriately obtained.

[0032] The solid content of the latex composition is 60% by weight or more, preferably 60 to 75% by weight, and more preferably 60 to 70% by weight. If the solid content is too low, the shrinkage rate during molding becomes too high, resulting in poor manufacturing stability and dimensional stability.

[0033] The viscosity of the latex composition at 25°C is 1500 cps or less, preferably 1200 cps or less, more preferably 1000 cps or less. The lower limit of the viscosity is not particularly limited, but is preferably 100 cps. If the viscosity is too high, the gelling property becomes very poor, and foam rubber cannot be properly obtained. The viscosity of the latex composition of the present invention at 25°C can be measured using a B-type viscometer at a temperature of 25°C and a rotation speed of 60 rpm. The latex composition of the present invention has a solid content concentration of 60% by weight or more, and the viscosity at 25° C. at that solid content concentration (for example, a solid content concentration actually used) may be within the above range, but when the solid content concentration is 65% by weight, the viscosity at 25° C. is preferably within the above range. In this case, when the solid content concentration of the latex composition is less than 65% by weight, the solid content concentration can be adjusted by a concentration operation using a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration, etc., and when the solid content concentration of the latex composition exceeds 65% by weight, the solid content concentration can be adjusted by diluting the composition with water, and then the viscosity can be measured.

[0034] The number average particle size of the polymer particles in the polymer latex contained in the latex composition of the present invention is not particularly limited, but is preferably 100 to 600 nm, more preferably 150 to 600 nm, and even more preferably 200 to 500 nm. When the number average molecular weight of the polymer particles is within the above range, the storage stability of the latex composition can be further improved. The number average particle size of the polymer particles in the polymer latex contained in the latex composition of the present invention can be measured using a light scattering diffraction particle size measuring device (model "LS-13320", manufactured by Beckman Coulter, Inc.). When the polymer latex contained in the latex composition is a polymer latex obtained by emulsion polymerization and has a particle size enlarged by performing a predetermined enlargement treatment, the particle size of the polymer particles constituting the enlarged polymer latex may be within the above range.

[0035] The latex composition of the present invention may contain a crosslinking agent.

[0036] Examples of crosslinking agents include powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, N,N'-dithio-bis(hexahydro-2H-azepinone-2), phosphorus-containing polysulfide, polymeric polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The crosslinking agents can be used alone or in combination of two or more.

[0037] The content of the crosslinking agent in the latex composition is not particularly limited, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the polymer component in the latex composition. By setting the content of the crosslinking agent within the above range, the strength of the obtained foam rubber can be increased.

[0038] In addition, the latex composition of the present invention preferably further contains a crosslinking accelerator.

[0039] As the crosslinking accelerator, those commonly used in the production of foam rubber can be used, for example, dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2 ,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholino dithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, 1,3-bis(2-benzothiazyl mercaptomethyl)urea, etc., but zinc diethyldithiocarbamate, zinc 2-dibutyldithiocarbamate, and zinc 2-mercaptobenzothiazole are preferred. The crosslinking accelerator can be used alone or in combination of two or more.

[0040] The content of the crosslinking accelerator is preferably 0.05 to 5 parts by weight, more preferably 0.1 to 2 parts by weight, based on 100 parts by weight of the polymer component in the latex composition. By setting the content of the crosslinking accelerator within the above range, the strength of the obtained foam rubber can be increased.

[0041] In addition, the latex composition of the present invention preferably further contains zinc oxide.

[0042] The content of zinc oxide is not particularly limited, but is preferably 0.1 to 5 parts by weight, more preferably 0.2 to 2 parts by weight, based on 100 parts by weight of the polymer contained in the latex composition. By setting the content of zinc oxide within the above range, the strength of the obtained foam rubber can be increased.

[0043] The latex composition of the present invention may further contain a foam stabilizer, a chelating agent, an oxygen scavenger, an antioxidant, a preservative, an antibacterial agent, an antifoaming agent, a colorant, a thickener, a reinforcing agent such as carbon black, silica, or talc, a filler such as calcium carbonate or clay, an ultraviolet absorbing agent, a plasticizer, a pH adjuster, or the like.

[0044] The bubble stabilizer may be one that is commonly used in the manufacture of foam rubber, such as ethyl chloride-formaldehyde-ammonia reaction products (e.g., trade name "Trimenbase", manufactured by Crompton Corp.), hexafluorosilicate, etc. The amount of the bubble stabilizer is preferably 0.4 to 10 parts by weight, more preferably 0.4 to 6 parts by weight, based on 100 parts by weight of the polymer component in the latex composition. By setting the amount of the bubble stabilizer within the above range, the bubbles contained in the obtained foam rubber can be made fine and uniform, and flexibility and strength can be improved.

[0045] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.

[0046] The method for producing the latex composition of the present invention is not particularly limited, but it can be produced by the following method.

[0047] In one embodiment of the present invention, a method for producing a latex composition includes the steps of: A preparation step of preparing a polymer latex; and a particle size enlargement / concentration step of adding an alkali metal salt of a divalent or higher polybasic acid to the polymer latex and concentrating the mixture to obtain a latex composition containing an enlarged polymer latex, having a solid content of 60% by weight or more, and having a viscosity of 1500 cps or less at 25°C. According to such a production method, it is possible to obtain a latex composition containing an enlarged polymer latex and an alkali metal salt of a divalent or higher polybasic acid.

[0048] (Preparation process) The method for preparing the polymer latex contained in the latex composition of the present invention is not particularly limited, and any conventionally known method can be adopted. Examples of the method for preparing a polymer latex in which polymer particles are dispersed in water include a method of emulsion polymerizing the above-mentioned monomers, a method of emulsifying a polymer solution obtained by solution polymerizing the above-mentioned monomers in water in the presence of an emulsifier and removing an organic solvent as necessary, and a method of emulsifying a polymer solution or an aqueous dispersion of a polymer in which a solid polymer is dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier and removing an organic solvent as necessary. Among these, from the viewpoint of productivity, a method of obtaining a polymer latex by emulsion polymerizing a monomer is preferred. That is, in the preparation step, it is preferred to emulsion polymerize a monomer.

[0049] The method for obtaining a polymer latex by emulsion polymerization of a monomer may be any method in which the monomer is emulsion polymerized in water in the presence of an emulsifier, and any conventionally known method may be used. In this case, the monomers may be the above-mentioned monomers in the above-mentioned ratio. In addition, for example, when emulsion polymerizing a monomer, polymerization auxiliary materials such as a polymerization initiator, a chelating agent, an oxygen scavenger, a molecular weight regulator, and a pH regulator that are commonly used may be used. The method for adding these polymerization auxiliary materials is not particularly limited, and any method such as an initial lump addition method, a divided addition method, or a continuous addition method may be used.

[0050] The emulsifier is not particularly limited, and examples thereof include anionic emulsifiers and nonionic emulsifiers. Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include emulsifiers such as polyethylene glycol ester type and Pluronic (registered trademark) type such as block copolymers of ethylene oxide and propylene oxide. Among these, resin acid salts or fatty acid salts are preferred, and at least one selected from the group consisting of potassium rosinate, sodium rosinate, potassium oleate, and sodium oleate is more preferred, and potassium oleate is even more preferred. Moreover, these emulsifiers can be used alone or in combination of two or more. The amount of the emulsifier used is preferably 0.5 parts by weight or more and less than 10 parts by weight, more preferably 1 to 9 parts by weight, even more preferably 1 to 5 parts by weight, and even more preferably 1 to 4 parts by weight, based on 100 parts by weight of the monomer used in the polymerization.

[0051] The polymerization initiator is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 2 parts by weight, based on 100 parts by weight of the monomer used in the polymerization.

[0052] The peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but includes compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; and amine compounds such as dimethylaniline. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight per 100 parts by weight of the peroxide.

[0053] Examples of the molecular weight regulator include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-stearyl mercaptan; xanthogen compounds such as dimethyl xanthogen disulfide and diisopropyl xanthogen disulfide; thiuram compounds such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide; 2,6-di-t-butyl-4- Examples of the molecular weight regulator include phenolic compounds such as methylphenol and styrenated phenol; allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; α-benzyloxystyrene, α-benzyloxyacrylonitrile, α-benzyloxyacrylamide, triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, thiomalic acid, 2-ethylhexyl thioglycolate, α-methylstyrene dimer, and terpinolene. These molecular weight regulators can be used alone or in combination of two or more. The amount of the molecular weight regulator used is preferably 0.1 to 3 parts by weight, more preferably 0.2 to 2 parts by weight, and particularly preferably 0.3 to 1.5 parts by weight, based on 100 parts by weight of the monomer used in the polymerization. By setting the amount of the molecular weight regulator to the above range, the strength of the foam rubber obtained can be improved.

[0054] The amount of water used in emulsion polymerization is preferably 80 to 600 parts by weight, more preferably 100 to 200 parts by weight, based on 100 parts by weight of the monomer used in the polymerization.

[0055] The emulsion polymerization reaction may be either continuous or batchwise, and the polymerization time is not particularly limited. The monomer addition method may include, for example, a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then adding the remaining monomers continuously or intermittently to polymerize them, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, the various monomers to be used may be mixed in advance and then added to the reaction vessel, or each monomer may be added to the reaction vessel separately. In addition, when producing a latex of a nitrile group-containing conjugated diene copolymer as a polymer latex, when using a method of adding a part of the monomer to a reactor after starting the polymerization reaction and continuing the polymerization, for example, a method of adding a part of the ethylenically unsaturated nitrile monomer and the conjugated diene monomer to a reactor, starting the polymerization reaction, and then adding the remaining part of the conjugated diene monomer to the reactor at once or in portions while the polymerization reaction rate in the reactor is 20 to 65%, and continuing the polymerization reaction further can be mentioned. In this case, the ratio of the conjugated diene monomer added after starting the polymerization reaction is preferably 20 to 60% by weight of the total amount of the conjugated diene monomer used for polymerization.

[0056] As described above, the monomer mixture is emulsion-polymerized, and when a predetermined polymerization conversion rate is reached, the polymerization reaction is stopped by cooling the polymerization system or adding a polymerization terminator. The polymerization conversion rate at the time of stopping the polymerization is not particularly limited, but is preferably 75% by weight or more. If the polymerization conversion rate is too low or too high, the productivity tends to decrease. The polymerization temperature is not particularly limited, but is preferably 0 to 50°C, more preferably 5 to 35°C.

[0057] The polymerization terminator is not particularly limited, but examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, and aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzenedithiocarboxylic acid, and hydroxydibutylbenzenedithiocarboxylic acid, and their alkali metal salts. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight based on 100 parts by weight of the monomer used in the polymerization.

[0058] By carrying out the polymerization reaction as described above, a polymer latex in which polymer particles are dispersed in water can be obtained. If necessary, unreacted monomers may be removed from the polymer latex.

[0059] The number average particle size of the polymer particles in the polymer latex obtained by emulsion polymerization is preferably 400 nm or less. From the viewpoint of productivity of the latex composition, the number average particle size of the polymer particles is preferably 50 nm or more and 300 nm or less, more preferably 50 nm or more and 250 nm or less. The number average particle size of the rubber particles can be measured using a light scattering diffraction particle size measuring device (model "LS-13320", manufactured by Beckman Coulter).

[0060] When a polymer latex is obtained by emulsion polymerization of a monomer, the number average particle size of the polymer particles can be controlled by adjusting polymerization conditions such as the type and amount of an emulsifier, the type and amount of an initiator, the amount of water, polymerization time, etc. When a polymer latex is obtained by emulsifying a polymer solution or an aqueous polymer dispersion in water in the presence of an emulsifier, the number average particle size can be controlled by adjusting emulsification conditions such as the type and amount of an emulsifier, the amount of water, and mixing conditions of the polymer solution or aqueous polymer dispersion with water.

[0061] The solid content concentration of the polymer latex is usually 10% by weight to 50% by weight. The solid content concentration of the polymer latex may be less than 40% by weight. The solid content concentration of the polymer latex can be measured by the method described later as a method for measuring the solid content concentration of a stabilized latex.

[0062] (Stabilization process) The method for producing a latex composition of the present invention may include a stabilization step of adding the above-mentioned surfactant having a sulfonate structure to obtain a stabilized latex, as necessary. In the stabilization step, the surfactant having a sulfonate structure may be added to the polymer latex obtained in the above-mentioned preparation step in a ratio of 0.15 parts by weight or more and less than 5.0 parts by weight per 100 parts by weight of the polymer component. The amount of the surfactant having a sulfonate structure added is more preferably 0.1 to 4.0 parts by weight, and even more preferably 1.0 to 3.0 parts by weight, per 100 parts by weight of the polymer component.

[0063] In the stabilization step, it is preferable to adjust the solid content concentration of the polymer latex to be in the range of 40% by weight or more and less than 60% by weight by adjusting the solid content concentration of the polymer latex as necessary before or after adding the surfactant having a sulfonate structure to the polymer latex.

[0064] The solids concentration of the polymer latex can be adjusted by concentrating or diluting the polymer latex depending on the solids concentration of the polymer latex obtained in the preparation step, without any particular limitation.

[0065] The method for concentrating the polymer latex is not particularly limited, and examples thereof include vacuum distillation, atmospheric distillation, centrifugation, membrane concentration, etc. As a method for concentrating the polymer latex, distillation is preferred, and vacuum distillation is more preferred, since it can produce a latex with excellent storage stability, gelling property, and shrinkage suppression property during foam rubber molding with higher productivity. In addition, a method for diluting the polymer latex includes a method of adding water.

[0066] The temperature during distillation is preferably 30° C. to 100° C., more preferably 40° C. to 90° C. The pressure (gauge pressure) during distillation is preferably −0.1 to 0.0 MPa, more preferably −0.05 to −0.099 MPa.

[0067] The centrifugation is preferably carried out, for example, using a continuous centrifuge under conditions of a centrifugal force of preferably 100 to 10,000 G, a solids concentration of the polymer latex before centrifugation of preferably 2 to 15% by weight, a flow rate fed to the centrifuge of preferably 500 to 1700 kg / hr, and a back pressure (gauge pressure) of the centrifuge of preferably 0.03 to 1.6 MPa, and a stabilized latex can be obtained as a light liquid after centrifugation.

[0068] The solid content concentration of the stabilized latex is preferably 20 to 55% by weight, more preferably 25 to 50% by weight, since a latex for foam rubber having excellent storage stability, gelling property, and shrinkage suppression property during foam rubber molding can be produced with higher productivity.

[0069] (Particle size enlargement / concentration process) The method for producing a latex composition of the present invention includes a particle size enlargement / concentration step of adding an alkali metal salt of a divalent or higher polybasic acid to the polymer latex obtained through the preparation step and the optional stabilization step to concentrate the polymer latex. In the particle size enlargement / concentration step, the amount of the alkali metal salt of a divalent or higher polybasic acid added is in the range of 0.5 to 20 parts by weight per 100 parts by weight of the polymer component in the polymer latex.

[0070] According to the particle size enlargement / concentration step, the polymer particles constituting the polymer latex obtained through the preparation step and the optional stabilization step can be unified and the particle size can be enlarged by the action of the alkali metal salt of divalent or higher polybasic acid added in the range of 0.5-20 parts by weight relative to 100 parts by weight of the polymer component in the polymer latex and the concentration, thereby obtaining a composition containing an enlarged polymer latex. According to the production method of the present invention, the particle size is enlarged and concentrated through the particle size enlargement / concentration step, so that the solid content concentration can be 60% by weight or more and the viscosity at 25°C can be 1500 cps or less.

[0071] In the particle size enlargement and concentration process, if the amount of the alkali metal salt of a polybasic acid having a valence of 2 or more relative to 100 parts by weight of the polymer component in the polymer latex is less than 0.5 parts by weight, the particle size does not enlarge sufficiently, and when the solid content concentration of the latex composition is 60% by weight or more, the viscosity becomes too high, and the storage stability, gelling property, and foam rubber moldability tend to be poor. Also, if the amount of the alkali metal salt of a polybasic acid having a valence of 2 or more relative to 100 parts by weight of the polymer component in the polymer latex exceeds 20 parts by weight, the coagulation of the alkali metal salt of a polybasic acid having a valence of 2 or more relative to 100 parts by weight of the polymer component progresses rather than the enlargement of the polymer particles, making it difficult to maintain the latex state. The amount of the alkali metal salt of a divalent or higher polybasic acid added in the particle size enlargement and concentration process is preferably 0.5 parts by weight or more and less than 10 parts by weight, more preferably 0.5 to 5 parts by weight, based on 100 parts by weight of the polymer component in the polymer latex.

[0072] When the alkali metal salt of a divalent or higher polybasic acid is added to the polymer latex, the entire amount of the alkali metal salt of the divalent or higher polybasic acid may be added at once, the alkali metal salt of the divalent or higher polybasic acid may be added in several divided portions, or the alkali metal salt of the divalent or higher polybasic acid may be added continuously. From the viewpoint of the stability of the obtained latex composition, the method of adding the alkali metal salt of the divalent or higher polybasic acid in several divided portions to the stabilized latex, or the method of adding the alkali metal salt of the divalent or higher polybasic acid continuously to the stabilized latex is preferred.

[0073] In the method of adding the alkali metal salt of a divalent or higher polybasic acid to the polymer latex in several divided portions or the method of adding the alkali metal salt of a divalent or higher polybasic acid continuously to the polymer latex, the time from the start of the addition of the alkali metal salt of a divalent or higher polybasic acid to the polymer latex to the end of the addition is preferably 0.5 to 120 minutes, more preferably 0.5 to 60 minutes, in order to produce a latex composition having excellent gelling properties and shrinkage suppression properties during foam molding with higher productivity.

[0074] In the particle size enlargement and concentration process, it is preferable to add an alkali metal salt of a divalent or higher polybasic acid while stirring the polymer latex, since this allows for the production of a latex composition having excellent storage stability, gelling properties, and shrinkage suppression properties during foam rubber molding with higher productivity. As a method for stirring the polymer latex, for example, a method of stirring at a rotation speed of 50 to 2,500 rpm using a stirring device such as a paddle-type stirring blade can be mentioned.

[0075] In the particle size enlargement and concentration step, the polymer latex may be stirred after adding an alkali metal salt of a divalent or higher polybasic acid to the polymer latex. As for the stirring conditions of the latex composition after adding the salt of a divalent or higher polybasic acid and an alkali metal, the rotation speed is preferably 50 to 2,500 rpm, more preferably 50 to 1,000 rpm, and the stirring time is preferably 0.5 to 12 hours, more preferably 0.5 to 5 hours, in order to produce a latex composition having excellent storage stability, gelling properties, and shrinkage suppression properties during foam rubber molding with higher productivity.

[0076] The method of adding the salt of the divalent or higher polybasic acid and the alkali metal to the polymer latex includes a method of adding the alkali metal salt of the divalent or higher polybasic acid directly to the polymer latex, and a method of preparing a solution or dispersion of the alkali metal salt of the divalent or higher polybasic acid and adding the obtained solution or dispersion to the polymer latex. From the viewpoint of stability and productivity of the latex composition, a method of preparing a solution or dispersion of the alkali metal salt of the divalent or higher polybasic acid and adding the obtained solution or dispersion to the polymer latex is preferred. The concentration of the salt in the solution or dispersion of the alkali metal salt of the divalent or higher polybasic acid may be appropriately determined depending on the type of the alkali metal salt of the divalent or higher polybasic acid and the solid content concentration of the stabilized latex, but from the viewpoint of storage stability, gelling property, stability and productivity of the latex composition, it is preferably 0.5% by weight to 15% by weight, more preferably 0.5% by weight to 10% by weight.

[0077] As described above, after adding an alkali metal salt of a divalent or higher polybasic acid to a polymer latex, the composition containing the polymer latex and an alkali metal salt of a divalent or higher polybasic acid is concentrated to obtain a latex composition having a solid content concentration of 60% by weight or more and a viscosity of 1500 cps or less at 25°C. The composition containing the polymer latex and an alkali metal salt of a divalent or higher polybasic acid has excellent fluidity when concentrated, and the solid content concentration can be easily made 60% by weight or more (a solid content concentration suitable for foam rubber production applications). By concentrating the solid content concentration of the latex composition to 60% by weight or more, the latex composition can be made more excellent in shrinkage suppression during foam rubber molding, and further, the quality of the obtained foam rubber (for example, the uniformity and strength of bubbles) can be improved.

[0078] As a method for concentrating a composition containing a polymer latex and an alkali metal salt of a dibasic acid having a valence of 2 or more, the above-mentioned method and its conditions for concentrating a polymer latex can be appropriately adopted. As a method for concentrating a composition containing a polymer latex and an alkali metal salt of a dibasic acid having a valence of 2 or more, distillation is preferred, and reduced pressure distillation is more preferred, since it can produce a latex composition having excellent storage stability, gelling property, and shrinkage suppression property during foam rubber molding with higher productivity.

[0079] <Foam rubber> The foam rubber of the present invention is obtained by using the above-mentioned latex composition of the present invention. The latex composition of the present invention is excellent in storage stability, gelling property, and shrinkage suppression during foam rubber molding. Therefore, by using the latex composition of the present invention, high-quality foam rubber with suppressed shrinkage can be produced with high productivity. As a method for producing foam rubber, a production method in which the latex composition of the present invention is foamed and solidified is preferable.

[0080] When foaming the latex composition of the present invention, air is usually used. For example, the latex composition can be foamed by stirring and incorporating air. In this case, for example, an Oakes foaming machine, an ultrasonic foaming machine, or the like can be used. In addition, a carbonate such as ammonium carbonate or sodium bicarbonate; an azo compound such as azodicarboxylic acid amide or azobisisobutyronitrile; or a gas generating substance such as benzenesulfonyl hydrazide can be added to the latex composition of the present invention to foam it.

[0081] After foaming the latex composition of the present invention to obtain a foam, it is preferable to solidify the foam in order to fix the foamed state. The solidification method may be any method capable of gelling and solidifying the foam, and a conventionally known method may be used. For example, the Dunlop method (ambient temperature solidification method) in which a room temperature solidification agent such as sodium hexafluorosilicate (sodium silicofluoride), potassium hexafluorosilicate (potassium silicofluoride), or a fluoride silicon compound such as titanic sodium silicofluoride is added to the foam; the heat-sensitive solidification method in which a heat-sensitive solidification agent such as organopolysiloxane, polyvinyl methyl ether, or zinc ammonium sulfate complex salt is added to the foam; or the freeze solidification method may be used. The amount of the coagulant such as the room temperature coagulant or the heat-sensitive coagulant is not particularly limited, but is preferably 0.5 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, based on 100 parts by weight of the polymer component in the foam.

[0082] After adding a coagulant to the foam, the foam is transferred to a mold of a desired shape and coagulated to obtain foam rubber. After coagulation, the foam may be heated to crosslink. The crosslinking conditions are preferably a temperature of 100 to 160°C and a heat treatment time of preferably 15 to 120 minutes.

[0083] The foam rubber thus obtained is preferably washed after being removed from the mold. The washing method is not particularly limited, but may be, for example, a method of washing with water at about 20 to 70°C using a washing machine or the like and stirring for about 5 to 15 minutes. After washing, it is preferable to drain the water and dry at a temperature of about 30 to 90°C so as not to damage the texture of the foam rubber. The foam rubber thus obtained can be used as a puff (cosmetic sponge) or the like by, for example, slicing it to a predetermined thickness and cutting it into a predetermined shape, and then grinding the sides with a rotating grindstone or the like.

[0084] The foam rubber obtained by using the latex composition of the present invention can be suitably used for various applications such as mattresses, puffs (cosmetic sponges), rolls, and impact absorbers. EXAMPLES

[0085] The present invention will be described below in more detail with reference to examples, but the present invention is not limited to these examples. In the following, "parts" and "%" are by weight unless otherwise specified. Tests and evaluations were performed according to the following.

[0086] <Amount of aggregates> After measuring the solid content concentration of the latex composition, about 100 g of the latex composition was weighed and filtered through a SUS wire net with a known weight of 80 mesh, and the aggregates on the wire net were washed with water several times to remove the latex composition. This was dried at 105°C for 60 minutes, and the dry weight was measured, and the content of the aggregates was calculated as a percentage when the amount of the polymer component contained in the latex composition was taken as 100% (unit: %). The lower the content of the aggregates, the more excellent the stability of the latex composition.

[0087] <Solid content concentration> 2 g of the sample was weighed out (weight: X2) onto an aluminum dish (weight: X1), and dried for 2 hours in a hot air dryer at 105° C. Then, after cooling in a desiccator, the weight of the aluminum dish was measured (weight: X3), and the solid content was calculated according to the following formula. Solid content concentration (%)=(X3-X1)×100 / X2

[0088] <Number average particle size of polymer particles> The number average particle size (nm) of the polymer particles constituting the latex composition was determined using a light scattering diffraction particle size analyzer (model "LS-13320", manufactured by Beckman Coulter, Inc.).

[0089] <Viscosity> For the latex compositions after the enlargement treatment obtained in each of the Examples and Comparative Examples, the Brookfield viscosity was measured by using a Brookfield viscometer at a rotation speed of 60 rpm at a temperature of 25°C.

[0090] <Amount of aggregates after centrifugation> 30 g of the latex composition after the thickening treatment obtained in each Example and Comparative Example was centrifuged at 1000 G using a centrifuge (product name "H-2000B", manufactured by Kokusan Co., Ltd.). Then, it was filtered through a SUS wire mesh of 80 mesh with a known weight, and the aggregates on the wire mesh were washed with water several times to remove the latex composition. After drying at 105°C for 60 minutes, the dry weight was measured, and the content of the aggregates was calculated as a percentage when the amount of the polymer component contained in the latex composition was taken as 100% (unit: %). The lower the content of the aggregates, the more excellent the stability of the latex composition.

[0091] <Gelation time> To 100 parts of the polymer component in the latex composition, 4 parts of a vulcanization system aqueous dispersion (colloidal sulfur / dithiocarbamate vulcanization accelerator Noccelaer EZ (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) / thiazole vulcanization accelerator Noccelaer MZ (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) = 2 / 1 / 1 (weight ratio, solid content concentration 50%), 3 parts of a zinc oxide aqueous dispersion (solid content concentration 50%), and 1 part of a foam stabilizer (Trimenebase: manufactured by Crompton Corp.) were added and thoroughly dispersed to obtain a latex composition. The gelation time of the obtained latex composition was evaluated according to the following method. The latex was stirred and foamed using a stand mixer (Electrolux, ESM945) to obtain a foam having a volume 5.0 times the volume before stirring. An aqueous dispersion of sodium silicofluoride (solid content concentration 20% by weight) was added to the obtained foam so that the amount of sodium silicofluoride added was 1.5 parts per 100 parts of the polymer component in the obtained foam, and the foam was further stirred for 1 minute to obtain a gelling foam. The time from when the gelling foam was obtained until the gelling foam no longer adhered to the hand when touched was measured, and the evaluation was based on the following criteria. A: The gelation time was within 5 minutes. △: The gelation time was more than 5 minutes and less than 10 minutes. ×: The gelation time was more than 10 minutes. The shorter the gelation time, the better the gelling property of the latex.

[0092] <Foam rubber moldability> In all the examples and comparative examples, a petri dish of the same shape was used. A gelling foam was obtained at the same time as the gelling time measurement. The gelling foam was poured into the petri dish to a predetermined height (i.e., the height of the foam before crosslinking), and crosslinked at 110°C for 40 minutes. The height of the crosslinked product was measured and evaluated according to the following criteria. ○: Decay rate less than 10% ×: Attenuation rate 10% or more

[0093] <Example 1> (Preparation process) In a pressure-resistant reactor, 200 parts of water, 1 part of potassium oleate (OLK), 55 parts of acrylonitrile, 0.5 parts of t-dodecyl mercaptan, 0.03 parts of sodium formaldehyde sulfoxylate, 0.003 parts of ferrous sulfate, and 0.008 parts of sodium ethylenediaminetetraacetate were added, and after sufficient degassing, 25 parts of 1,3-butadiene were added. Next, 0.05 parts of cumene hydroperoxide were added as a polymerization initiator, and emulsion polymerization was started at a reaction temperature of 5°C. When the polymerization conversion rate reached 40%, 10 parts of 1,3-butadiene were added, and the polymerization reaction was continued. Furthermore, when the polymerization conversion rate reached 60%, 10 parts of 1,3-butadiene were added, and the polymerization reaction was continued. When the polymerization conversion rate reached 80%, a polymerization terminator solution consisting of 0.25 parts of diethylhydroxylamine and 5 parts of water was added to terminate the polymerization reaction, and the unreacted monomer was removed to obtain a polymer latex. The number average particle size of the polymer particles in the polymer latex was 90 nm.

[0094] (Stabilization process) To the obtained polymer latex, an aqueous solution of NASF (a 45% by weight aqueous solution of sodium salt of β-naphthalenesulfonic acid formalin condensate (NASF), product name "Demol T-45", manufactured by Kao Corporation) was added so that the amount of NASF was 2 parts per 100 parts of the polymer component, and then the mixture was heated at 70°C under reduced pressure of -0.05 MPa (gauge pressure) to obtain a stabilized latex.

[0095] (Particle size enlargement / concentration process) To the obtained stabilized latex, 0.01 parts of modified hydrocarbon oil based on mineral oil (trade name "DF714S", manufactured by Seiko PMC Co., Ltd.) was added as an antifoaming agent, and the mixture was stirred at a rotation speed of 100 rpm using a paddle-type stirring blade. While continuing the stirring, tripotassium phosphate was added so that the ratio of tripotassium phosphate to 100 parts of stabilized latex was 0.5 parts. The tripotassium phosphate was added in several divided portions, and the time from the start of the addition of tripotassium phosphate to the end of the addition was 30 minutes. After the addition of tripotassium phosphate was completed, the mixture was stirred for 1.0 hour, and then heated at 80°C under a reduced pressure condition of -0.05 MPa (gauge pressure) to concentrate, to obtain a latex composition with a solid content concentration of 65% by weight. The latex composition had excellent fluidity. The latex composition was measured and evaluated according to the above-mentioned method for the amount of aggregates after concentration, the solid content concentration, the number average particle size of the polymer particles, the viscosity, the amount of aggregates after centrifugation, the gelation time, and the moldability during foam rubber molding. The results are shown in Table 1.

[0096] <Example 2> A latex composition was obtained in the same manner as in Example 1, except that the amount of potassium oleate in the preparation step was changed to 3 parts, the stabilization step was not performed, and the amount of tripotassium phosphate in the particle size enlargement and concentration step was changed to 1 part. The latex composition had excellent fluidity. The results of measurement and evaluation in the same manner as in Example 1 are shown in Table 1.

[0097] <Example 3> A latex composition was obtained in the same manner as in Example 1, except that the amount of potassium oleate in the preparation process was changed to 3 parts, the NASF aqueous solution in the stabilization process was changed to PELLEX NBL (aqueous solution of sodium alkylnaphthalenesulfonate with a concentration of 35% by weight, manufactured by Kao Corporation), and the amount of tripotassium phosphate in the particle size enlargement and concentration process was changed to 5 parts. The latex composition had excellent fluidity. The results of measurement and evaluation in the same manner as in Example 1 are shown in Table 1.

[0098] <Example 4> A latex composition was obtained in the same manner as in Example 3, except that tripotassium phosphate in the particle size enlargement and concentration step was changed to potassium sulfate, and the amount of potassium sulfate added was changed to 1 part per 100 parts of the polymer component in the polymer latex. The latex composition had excellent flowability. The results of measurement and evaluation in the same manner as in Example 1 are shown in Table 1.

[0099] <Comparative Example 1> Except for changing the amount of potassium oleate in the preparation step to 10 parts, not performing the stabilization step, and changing the amount of tripotassium phosphate in the particle size enlargement and concentration step to 5 parts, the procedure was the same as in Example 1 to obtain an enlarged polymer latex. When the obtained enlarged polymer latex was heated at 70°C under reduced pressure of -0.05 MPa (gauge pressure), the latex was significantly thickened, and when the solid content reached 58% by weight, concentration became difficult. Therefore, heating was stopped to obtain a latex composition. The results of measurement and evaluation in the same manner as in Example 1 are shown in Table 1.

[0100] <Comparative Example 2> A latex composition was obtained in the same manner as in Example 1, except that the amount of the NASF aqueous solution added in the stabilization step was changed to an amount such that the amount of NASF was 5 parts per 100 parts of the polymer component in the polymer latex, and the amount of tripotassium phosphate in the particle size enlargement / concentration step was changed to 3.7 parts. The results of measurements and evaluations in the same manner as in Example 1 are shown in Table 1.

[0101] <Comparative Example 3> A latex for foam rubber was obtained in the same manner as in Example 1, except that sodium chloride (NaCl) was added in a ratio of 5 parts per 100 parts of the polymer component in the polymer latex instead of tripotassium phosphate in the particle size enlargement and concentration process. The results of measurement and evaluation in the same manner as in Example 1 are shown in Table 1.

[0102] [Table 1]

[0103] As shown in Table 1, by using a latex composition containing a polymer latex and a salt of a polybasic acid and an alkali metal, and having a specific range of solid content concentration and specific range of viscosity, a latex composition excellent in storage stability, gelling property, and moldability at the time of foam rubber molding could be obtained (Examples 1 to 4). It can be seen that the latex compositions of the examples have excellent storage stability because the amount of aggregates after centrifugation is suppressed and the stability of the latex is excellent.

[0104] On the other hand, when the solid content of the latex composition was less than 60% (Comparative Example 1) or when the viscosity of the latex composition at 25°C exceeded 1500 cps (Comparative Examples 1 and 2), the resulting latex composition had poor moldability during foam rubber molding. In Comparative Example 2, gelation did not occur.

[0105] In addition, when NaCl was used instead of the salt of polybasic acid and alkali metal (Comparative Example 3), the viscosity of the latex composition at 25°C exceeded 1500 cps and the composition was thickened, resulting in poor moldability during foam rubber molding.

Claims

1. The composition comprises a polymer latex and 0.5 to 20 parts by weight of an alkali metal salt of a divalent or higher polybasic acid relative to 100 parts by weight of a polymer component in the polymer latex, The solid content is 60% by weight or more, A latex composition having a viscosity of 1,500 cps or less at 25°C.

2. 2. The latex composition according to claim 1, wherein the polymer latex is a latex of a nitrile group-containing conjugated diene copolymer.

3. 3. The latex composition according to claim 1, having a viscosity at 25° C. of 1,000 cps or less.

4. The latex composition according to any one of claims 1 to 3, wherein the divalent or higher polybasic acid is at least one selected from the group consisting of phosphoric acid and sulfuric acid.

5. The latex composition of any one of claims 1 to 4, wherein the alkali metal is potassium.

6. A foam rubber obtained by foam molding the latex composition according to any one of claims 1 to 5.

7. A puff obtained by foam molding the latex composition according to any one of claims 1 to 5.

8. A method for preparing a polymer latex by emulsion polymerization of monomers in water in the presence of an emulsifier; a particle size enlargement / concentration step of adding an alkali metal salt of a divalent or higher polybasic acid to the polymer latex and concentrating the mixture to obtain a latex composition containing an enlarged polymer latex, having a solid content of 60% by weight or more and a viscosity of 1,500 cps or less at 25° C.; Equipped with The method may further include, as an optional step, a stabilization step of adding a surfactant having a sulfonate structure to the polymer latex in an amount of 0.15 parts by weight or more and less than 5.0 parts by weight based on 100 parts by weight of the polymer component in the polymer latex after the preparation step and before the particle size enlarging / concentrating step, In the preparation step, the amount of the emulsifier used is 0.5 parts by weight or more and less than 10 parts by weight based on 100 parts by weight of the monomer, In the particle size enlargement / concentration step, 0.5 to 20 parts by weight of the alkali metal salt of a divalent or higher polybasic acid is added to 100 parts by weight of a polymer component in the polymer latex.

Citation Information

Patent Citations

  • Receiving system for push-button dial signal

    JP1983059693A

  • Enlargement of particle of conjugated diene copolymer rubber latex

    JP1999060611A

  • Enlargemeny of particle of synthetic rubber latex

    JP1999060612A

  • Graft copolymer, thermoplastic resin composition containing the same, and molded product

    JP2004182830A

  • Copolymer latex composition for make-up puff

    JP2004262998A